2010
DOI: 10.1086/651076
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Associated Methicillin‐ResistantStaphylococcus aureusand HIV: Intersecting Epidemics

Abstract: HIV-infected patients are at markedly increased risk for CA-MRSA infection. This risk may be amplified by overlapping community networks of high-risk patients that may be targets for prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 35 publications
(33 reference statements)
8
93
0
1
Order By: Relevance
“…Several studies have reported an increased risk of MRSA colonization and infection in HIV-infected individuals compared with the general population [28][29][30][31][32]. The prevalence of MRSA in Denmark is low [16] and, correspondingly, rates were low among HIV-infected individuals and comparable to those in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increased risk of MRSA colonization and infection in HIV-infected individuals compared with the general population [28][29][30][31][32]. The prevalence of MRSA in Denmark is low [16] and, correspondingly, rates were low among HIV-infected individuals and comparable to those in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…At the Cook County Hospital and its associated clinics in Chicago, CA-MRSA and CA-MSSA (criteria for community-associated infections were not provided) SSTIs were retrospectively reviewed for 2000 to 2007, and population-based incidence estimates were calculated. HIV-infected patients were more likely to have CA-MRSA SSTIs than were non-HIV-infected patients (incidence of 952 versus 156/100,000 population; RR, 6.1; P Ͻ 0.001) (733).…”
Section: Military Populationsmentioning
confidence: 96%
“…In the last decade, a number of reports have described the disproportionate impact of CA-MRSA on people with HIV infection [7], and the high rate of recurrence of SSTIs in this population [8,9]. Previous reports examining the risk factors for SSTIs in HIV-infected cohorts have limited themselves to culture-positive SSTIs [10][11][12][13][14][15][16][17][18], have only described the characteristics of patients who developed SSTIs [10,14,16,17,19], or were performed in demographically restricted cohorts [10-13, 15, 20-22]. Furthermore, perhaps because of differences in study design, these reports have had conflicting results regarding the immunologic and epidemiologic factors associated with an elevated risk of SSTIs in this population, and the role that trimethoprim-sulfamethoxazole (TMP-SMX) prophylaxis for Pneumocystis or toxoplasmosis may play in mitigating this risk [23,24].…”
Section: Introductionmentioning
confidence: 99%